Transgender and Intersex: Theoretical, Practical, and Artistic Perspectives - Horlacher, Stefan; SpringerLink (Online service) (New York : Palgrave Macmillan US(Imprint), 2016)
This book takes both transgender and intersex positions into account and asks about commonalities and strategic alliances in terms of knowledge, theory, philosophy, art, and life experience. It strikes a balance between works on literature, film, photography, sports, law, and general theory, bringing together humanistic and social science approaches. Horlacher adopts a non-hierarchical perspective and asks how transgender and intersex issues are conceptualized from a variety of different viewpoints and to what extent artistic and creative discourses offer their own uniquely relevant forms of knowledge and expression. .
1 Introduction: Transgender and Intersex: Theoretical, Practical, and Artistic Perspectives Stefan Horlacher -- 2 Queer Europe: New Normative Values for Global LGBT Law Stephen Whittle and Lewis Turner -- 3 Fear, Loathing and Empty Gestures: UK Legislation on Sport and the Transgender Participant David McArdle -- 4 Intersex and Trans* Communities: Commonalities and Tensions Cary Gabriel Costello -- 5 Transgender and Intersex: Unavoidable Essentialism and the Normative Struggle for Recognition Sebastian Jansen -- 6 Trans*, Intersex, and the Question of Pregnancy: Beyond Repronormative Reproduction Nadyne Stritzke and Elisa Scaramuzza -- 7 Transgender in a Global Frame Jack Halberstam -- 8 INTER*me: An Inter-locution on the Body in Photography Del LaGrace Volcano and Jay Prosser with Eliza Steinbock -- 9 Hermaphrodite's Voice: Dealing with the Either-Or Attitude in Science, Law and the Arts Michael Groneberg -- 10 On the Intelligibility of Trans* and Intersex Characters in Contemporary British and American Fiction Mirjam M. Frotscher -- 11 Boys Don't Cry and Tomboy: A Comparative Analysis John Phillips.
Keywords: Sociology; Gender Studies